Peran Modal Sosial Zuriat Panopengan Dalam Menjaga Keberlanjutan Tradisi Manopeng di Kampung Banyiur - Tiara Agustina; Arif Rahman Hakim (Prodi Sosiologi FISIP ULM, 2023)
The manopeng tradition is a tradition carried on by the panopengan zuriat in Banyiur Village, which faced problems during the Covid-19 pandemic, which forced the manopeng tradition to be carried out in secret and the funding from the City Government was cut off. This study aims to find out and describe how the role of social capital owned by zuriat panopeng in Kampung Bayiur in maintaining the sustainability of the manopeng tradition in Kampung Banyiur. The research method used in this study is qualitative with a descriptive approach. Data repetition techniques used are interviews, observation, and documentation. To analyze the data using interactive models, namely data reduction, data presentation and drawing conclusions. This research was conducted on Jalan Banyiur Luar (Kampung Banyiur), Basirih Village, West Banjarmasin District. The results of the study show that: 1) zuriat's beliefs in carrying out the manopeng tradition, namely belief due to heredity, belief in the existence of supernatural beings, belief in reinforcements, potential as cultural tourism; 2) in carrying out the manopeng tradition there are several rules as guidelines for the zuriat, namely the rules for carrying out the manopeng ritual, the rules in the Panopeng zuriat family and the rules in the Banyiur Village community; 3) in re-organizing the post-pandemic manopeng tradition, the zuriat build relationships with the community by way of bepuan (joint venture). Zuriat Panopengan also did this by submitting proposals to several private and state agencies. This study concludes that the panopengan zuriat in Kampung Banyiur has strong social capital so that the manopeng tradition can survive to this day.